Evaluation of the Remaining Prestress Force and Center Negative Capacity of Ties Removed from Track after 25 Years - Scott, James D.; Peterman, Robert J.; Beck, B. Terry; Riding, Kyle A. (Rural Railroad Safety Center, Kansas State University., 2021)
A study was conducted to determine the amount of internal prestress force remaining in prestressed concrete railroad tie designs that have withstood a lifetime of service without problems. Twelve (12) different tie designs that had performed well in track for over 25 years with no signs of longitudinal splitting were evaluated. Four different experimental test methods were used to determine the remaining prestress force in these existing ties. These included the flexural crack reopening method, the newly developed direct tension method, the strain gage method, and measurement of the length change of wires extracted from the ties. Test results indicate that the direct tension test was the most accurate of the four methods, and that existing ties tended to have prestressing forces in the range of 82-93 kips.
Keywords: Infrastructure; Railroad ties; Residual prestress force; Shape factor; Prestressed concrete; High speed rail